Model Pengasuhan Anak Tenaga Kerja Wanita - Munifah Bahfen (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The purpose of this study is to find out what are the reasons for working abroad, who cares for their children and how their parenting style is. The method used in the study was qualitative with a case study in Panyingkiran village, Karawang. Enculturation has taken place Women working abroad are desperate. The money from working abroad is used to improve the welfare of his extended family so that a surrogate role is needed for the mother in raising children. Parenting is handed over to large families, especially grandmothers. Mothers use the device of communication to keep participating in care even though the mother and child live far apart. Almost every night the mother communicates with the child, so that the child's behavior becomes independent, and is responsible.